2010
DOI: 10.1002/j.2161-1939.2010.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The Slaying of a Beautiful Hypothesis: The Efficacy of Counseling and the Therapeutic Process

Abstract: Although the efficacy of counseling has been empirically linked to the therapeutic process, the emphasis in much of the literature remains on technique use. This article discusses 3 components of therapeutic efficacy (i.e., common factors, working alliance, and counselor attributes) and provides implications for counselors and counselor training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…However, a common component of both frameworks is the therapeutic relationship (Budd & Hughes, 2009;Chambless & Hollon, 1998;Duncan et al, 2010;Hauser & Hays, 2010;Rosenzweig, 1936).…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
“…However, a common component of both frameworks is the therapeutic relationship (Budd & Hughes, 2009;Chambless & Hollon, 1998;Duncan et al, 2010;Hauser & Hays, 2010;Rosenzweig, 1936).…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
“…Research has suggested that counseling works regardless of therapeutic modality or theoretical orientation (Hauser & Hays, ; Nelson & Neufeldt, ; Wampold et al, ). There is relatively little difference in treatment outcomes or success rates among the different treatment models and theoretical approaches (Horvath & Greenberg, ).…”
mentioning
confidence: 99%
“…In humanistic practice, the understanding and examination of the counseling process through a common factors lens is widely accepted (Hauser & Hays, ). Common factors consist of extratherapeutic events, which account for 40% of change in therapy; therapeutic relationship, which accounts for 30% of change; hope and expectancy, which account for 15% of change; and therapeutic technique, which accounts for 15% of change.…”
mentioning
confidence: 99%
“…The concept dates back to Freud's (1913Freud's ( /1958 (Baldwin, Wampold, & Imel, 2007;Hauser & Hays, 2010).…”
Section: Definitionsmentioning
confidence: 99%
“…Some theories of psychotherapy view the therapeutic alliance as one of the strongest mechanisms of change (Barrett-Lennard, 1962;Rogers, 1957;Wampold, 2001), while other theories believe the alliance is necessary for change, but not a primary mechanism of change (Leichsenring, Hiller, Weissberg, & Leibing, 2006). Bordin's (1979) pantheoretical definition of the alliance receives continued use in recent research (Baldwin, Wampold, & Imel, 2007;Hauser & Hays, 2010). …”
Section: Definitionsmentioning
confidence: 99%